PHYSIOLOGICAL POTENTIAL FOR DESSICATED SOYBEAN SEED WITH DIQUAT AND PARAQUAT - KAPPES, Claudinei; CARVALHO, Marco Antônio Camillo de; YAMASHITA, Oscar Mitsuo (Scientia Agraria, 2009)
The type, mode of action and time when the desiccant is applied on soybean, are factors that can affect the physiological quality seeds. But if the operation is performed adequately, it may occur in anticipation of the harvest a few days, getting seeds of higher quality. This work aimed at evaluating the desiccant effect of pre-harvest in the physiological performance of soybean seed. The design was blocks at randomized in a factorial 3 x 4 (desiccants x time) with four replications. The desiccants were Diquat and Paraquat, both in the dose of 400 g.i.a. ha-1, + control (without desicantion). The times of application were in stages R6.0, R7.1, R7.2 and R7.3. Seeds were subjected to fermenation test, first count of germination, the germination speed rate, accelerated aging, cold testing and electrical conductivity. All tests were carried out at analysis seed laboratory analysis and technology of the University of the State of Mato Grosso. The desiccants were compared by Tukey (p<0.05). In spite of have provided anticipation of crop in only two days in relation to the control, the most favorable time to disecation, so much with Diquat as Paraquat, is at the stage R7.3, and disecateds lots with Paraquat presented better performance in some of the appraised quality tests.